2022
DOI: 10.3390/ijms232315343
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Pristine Carbon Nanotubes Toxicity in Rodent Models

Abstract: Carbon nanotubes are increasingly used in nanomedicine and material chemistry research, mostly because of their small size over a large surface area. Due to their properties, they are very attractive candidates for use in medicine and as drug carriers, contrast agents, biological platforms, and so forth. Carbon nanotubes (CNTs) may affect many organs, directly or indirectly, so there is a need for toxic effects evaluation. The main mechanisms of toxicity include oxidative stress, inflammation, the ability to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 118 publications
(135 reference statements)
0
8
0
Order By: Relevance
“…Tissues and organs are sampled and subjected to histopathological examination, revealing any morphological changes indicative of cellular damage, inflammation, or necrosis. For a comprehensive analysis of the in vivo CNM cytotoxicity, readers are encouraged to refer to recent reviews, as this is a heavily examined topic in previous reviews. , …”
Section: Biomedical and Environmental Translation Of Cnmsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tissues and organs are sampled and subjected to histopathological examination, revealing any morphological changes indicative of cellular damage, inflammation, or necrosis. For a comprehensive analysis of the in vivo CNM cytotoxicity, readers are encouraged to refer to recent reviews, as this is a heavily examined topic in previous reviews. , …”
Section: Biomedical and Environmental Translation Of Cnmsmentioning
confidence: 99%
“…For a comprehensive analysis of the in vivo CNM cytotoxicity, readers are encouraged to refer to recent reviews, as this is a heavily examined topic in previous reviews. 1314,1315 There is a recent study performed to determine the cytotoxicity of CDs in vivo, where researchers found that CDs synthesized from sugar cane molasses at concentrations lower than 150 μg/mL had no impact on embryonic toxicity nor showed impediment on embryo development in zebrafish. 1316 Conversely, concentrations higher than 200 μg/mL greatly increased cytotoxicity, and demonstrated an impact on the dopamine levels, and a decrease in TH + neuronal cells.…”
Section: Cytotoxicity Of Cnmsmentioning
confidence: 99%
“…By using nanocarrier systems, it may be possible to deliver anticancer drugs to cancer cells more efficiently, thereby improving treatment efficacy and reducing side effects. However, this research is still in its preliminary stages and further studies are needed to validate the effectiveness and safety of this approach ( Witkowska et al, 2022 ; Rashid et al, 2023 ).…”
Section: Carbon Nanotubes In Cancer Therapymentioning
confidence: 99%
“…The toxicology of carbon nanomaterials was studied for carbon nanotubes [1][2][3][4][5][6][7][8][9][10][11][12][13][14], graphene [15][16][17][18][19][20][21][22][23][24][25][26][27][28], fullerenes [29][30][31][32][33], and dots [34][35][36][37][38]. Most of the work deals with microorganisms, animals, and humans.…”
Section: Introductionmentioning
confidence: 99%